2021
DOI: 10.3389/fmicb.2021.667415
|View full text |Cite
|
Sign up to set email alerts
|

A Conjugative MDR pMG1-Like Plasmid Carrying the lsa(E) Gene of Enterococcus faecium With Potential Transmission to Staphylococcus aureus

Abstract: lsa(E) is a pleuromutilin, lincosamide, and streptogramin A (PLSA phenotype) resistance gene that was first described in S. aureus and was thought to have been transferred from Enterococcus sp. This study aimed to elucidate the prevalence of the lsa(E) gene among E. faecium isolates at a tertiary teaching hospital and to evaluate the transferability of the lsa(E) gene from E. faecium to S. aureus in vitro. A total of 96 E. faecium strains isolated from one hospital in Beijing in 2013 were analysed for quinupri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Noteworthy, the Q/D resistance mechanisms are still not perfectly understood. Indeed, few studies reported that resistance to streptogramin A is sufficient to confer resistance to Q/D (Hancock, 2005;Yan et al, 2021) while others support that a combination of both resistance to streptogramin A (vat or vga family) and streptogramin B (erm family or vgbB) is required to ensure Q/D resistance (Miller et al, 2014;Zarrouk 2000). Both lsaA and lsaE are the only genes reported to confer resistance to both Q/D components (Alcock et al, 2020;Singh et al, 2002;Wendlandt et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Noteworthy, the Q/D resistance mechanisms are still not perfectly understood. Indeed, few studies reported that resistance to streptogramin A is sufficient to confer resistance to Q/D (Hancock, 2005;Yan et al, 2021) while others support that a combination of both resistance to streptogramin A (vat or vga family) and streptogramin B (erm family or vgbB) is required to ensure Q/D resistance (Miller et al, 2014;Zarrouk 2000). Both lsaA and lsaE are the only genes reported to confer resistance to both Q/D components (Alcock et al, 2020;Singh et al, 2002;Wendlandt et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, lsaE and lnuB genes were flanked by one site-specific recombinase ( Figure 3 ), which could denote a previous event of mobilization and integration in the chromosome. In fact, Yan et al described these genes in a conjugative plasmid in Enterococcus faecium, potentially transmissible to Staphylococcus aureus [ 32 ]. These analyses also identified that both genes, lsaE and lnuB were located next to an antibiotic resistance region with ant(6)-I- sat-4 -aph(3′)-III clusters [ 33 ], as described herein.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have investigated that plasmids harboring linezolid resistance genes acquired from other enterococcal plasmids through MGE are associated with the MDR phenotype (Sadowy, 2018 ; Elghaieb et al, 2020 ). Conjugation of these genes was also evidenced from Enterococcus to Staphylococcus , elucidating their transmission potential (Yan et al, 2021 ). ARI3 carries two genes coding for aminoglycoside resistance ant1, apt_3 , and ant(6)-Ia , flanked by a putative recombinase and IS 4 family transposase IS Dha5 .…”
Section: Resultsmentioning
confidence: 99%